The development and types of social knowledge – continued - Hausner, Jerzy (Journal of Public Governance, 2013)
The paper recapitulates the discussion pursued at the Kraków Circle seminars, prompted by the first paper in this volume. The author engages in a dialogue with the authors of other papers published herein and develops his initial argumentation. At the same time, he indicates his preferred direction of subsequent debates within the Kraków Circle.